Wybrane aspekty bezpieczeństwa i jego zagrożeń w szkolnych relacjach pomiędzy uczniami - Kraszewska, Hanna; Silecka-Marek, Ewelina (Wydawnictwo Naukowe UAM, 2014)
The objective of this article is to discuss the issue of safety at school, which is one of the state’s education policy priorities. Aspects of school safety involve teachers as well as students and their parents or legal guardians, namely individuals who enter into various relationships and therefore can either support the issue of keeping the school a safe place, or be a source of conflict and risk.
Selected Aspects of Security and Threats in the School Relationships Between Learners
Keywords: education policy; safety; student; teacher; aggression; violence